2008
DOI: 10.1038/sj.onc.1211008
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of enhancement of TRAIL tumoricidal activity against human cancer cells of different origin by dipyridamole

Abstract: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) has emerged as an attractive cytokine that selectively targets cancer cells, however its efficacy has been challenged by a number of resistance mechanisms. Therefore, the current study investigated the potential of dipyridamole to enhance TRAIL efficacy and the probable underlying mechanisms. Dipyridamole dramatically sensitized p53-mutant human cancer cell lines: SW480, MG63 and DU145, to the antitumor activity of TRAIL, as evidenced by enabling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…It has been documented that some TZD decrease c‐FLIP39 or survivin expression,32, 40, 41 which contributes to enhancement of TRAIL‐induced apoptosis in certain types of cancer cells. We demonstrated that survivin expression is reduced in case of apoptosis or cell cycle arrest induction after TZD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented that some TZD decrease c‐FLIP39 or survivin expression,32, 40, 41 which contributes to enhancement of TRAIL‐induced apoptosis in certain types of cancer cells. We demonstrated that survivin expression is reduced in case of apoptosis or cell cycle arrest induction after TZD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, 2–14 promotes the proteasome-mediated degradation of survivin, a major hurdle to TRAIL signaling in these CRC cell lines [69]. Both CHOP-mediated DR5 increase and survivin down-regulation are also the major mechanisms by which dipyridamole, a thromboxane synthase inhibitor widely used as an antiplatelet, sensitizes SW480 cells to TRAIL [70]. …”
Section: Trail-sensitizing Agents In Crcmentioning
confidence: 99%
“…The XIAP, surviving, and LacZ siRNA were described previously (25,26) and synthesized by Proligo. GLO1 siRNA was purchased from Santa Cruz Biotechnology.…”
Section: Sirnasmentioning
confidence: 99%